Organizational Variables, Job Variables, And Job Stress: The Moderating Effect Of Personality Among Paiddealers Within The Stock Broking Firms In Penang - Yeoh, Chee Beng (2003)
The purpose of this study is to determine whether organizational variables (formalization, centralization, and organizational climate) and job variables (role conflict, role ambiguity, and role overload) affect job stress. Additionally, two personality variables (Type A personality and self-efficacy) were examined whether they serve to moderate the relationship between the independent variables and the dependent variable.